ADVANCED DVR CONTROL WITH IOT FOR VOLTAGE SAG COMPENSATION IN WIND-CONNECTED POWER GRIDS - R. C Ilambirai; T Kanthimathi; Raja Thimmarayan; B S Sagar (International Journal of Advances in Signal and Image Sciences, 2025)
An efficient approach for enhancing Power Quality (PQ) in wind grid-connected systems is proposed in this work. The proposed solution integrates an Internet of Things (IoT)-based monitoring system with a Dynamic Voltage Restorer (DVR) to mitigate voltage fluctuations commonly encountered in wind power generation systems. During voltage sags or swells, the DVR injects a compensating voltage in phase opposition to the grid disturbance, thereby maintaining voltage stability at the load end. The IoT-based monitoring component enables real-time data acquisition, analysis, and remote control, improving operational visibility and responsiveness. This integrated system offers several benefits, including enhanced power quality, improved system reliability, and reduced operational downtime. Simulation results validate the effectiveness of the proposed system in mitigating voltage sags and swells, demonstrating its potential as a practical and reliable solution for PQ enhancement in wind grid-connected systems. This research contributes meaningfully to the renewable energy domain by addressing critical power quality challenges associated with grid-connected wind energy infrastructures.